2021
DOI: 10.1109/jeds.2021.3057662
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Negative-Bias Temperature Instability in Si p-FinFETs With ALD W Gate-Filling Metal by Annealing Process Optimization

Abstract: In this paper, we present an experimental study on the impact of post-metallization annealing conditions on the negative-bias temperature instability (NBTI) of Si p-channel fin field-effect transistors (p-FinFETs) with atomic layer deposition tungsten (ALD W) as the gate-filling metal. The effects of annealing conditions on the tensile stress of the W film, impurity element concentration in the gate stack, fresh interface quality, threshold voltage shift (ΔVT), pre-existing traps (ΔNHT), generated traps, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Other types of III-V nanowires, e.g., InAs and GaSb, were also reported to be integrated for Si-GAAFETs. Among these studies, for example, Z. Zhu et al [336] reported a vertical NW p-MOSFET with the GaSb channel by applying digital etch (DE) schemes. Figure 37a shows the schematic of a single NW-GAA MOSFET.…”
Section: Iii-v Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Other types of III-V nanowires, e.g., InAs and GaSb, were also reported to be integrated for Si-GAAFETs. Among these studies, for example, Z. Zhu et al [336] reported a vertical NW p-MOSFET with the GaSb channel by applying digital etch (DE) schemes. Figure 37a shows the schematic of a single NW-GAA MOSFET.…”
Section: Iii-v Materialsmentioning
confidence: 99%
“…However, crystal quality optimization for Si-based III-V materials is still very challenging to achieve good device performance. prior to high-κ deposition [336]. Reproduced from [336], open access by ACS, 2022.…”
Section: Iii-v Materialsmentioning
confidence: 99%
See 3 more Smart Citations